2019
DOI: 10.21776/ub.jam.2019.017.01.09
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Experience in Building Satisfaction, Trust and Loyalty

Abstract: The purpose of this study is to explain the effect of experience on satisfaction, trust and loyalty. This study was conducted on inpatients service users in RSIA Puri Bunda Denpasar with a total of 100 respondents. Data analyzed with Partial Least Square technique. The results showed that experience, satisfaction and trust had a positive and significant effect on loyalty, experience had a positive and significant effect on satisfaction and experience had a positive and significant effect on trust. The implicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
1
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 9 publications
1
1
0
2
Order By: Relevance
“…When the quality of service matches consumer expectations the positive experience instills consumer trust in JNE. Hence, it is in accordance with studies (Mohmed et al, 2013;Chen et al, 2010;Chinomona, 2013;Pramita, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…When the quality of service matches consumer expectations the positive experience instills consumer trust in JNE. Hence, it is in accordance with studies (Mohmed et al, 2013;Chen et al, 2010;Chinomona, 2013;Pramita, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…As revealed in the present study, investors’ experience gained in company events with luxurious decoration and availability of valuable gifts is an effective way to build trust between them and the company. Moreover, satisfying investors’ initial requests can help build their trustful relationship with the company, thus bringing about financial benefits (Pramita, 2019). We found that most investors achieved a high financial return through their initial investments, and this motivated them to make subsequent investments based on the initial performance of the P2P company.…”
Section: Discussionmentioning
confidence: 99%
“…Menurut Bakker (2014), arousal terdiri dari tiga dimensi, yaitu sebagai berikut: stimulus fisik, motivasi intrinsik dan stimulus sikap. Pramita (2019), mendefinisikan kepuasan sebagai perasaan senang atau kecewa dari hasil membandingkan kinerja produk sesuai seperti yang diinginkan. Jika kinerja produk rendah dari yang diharapkan pelanggan akan kecewa.…”
Section: Arousalunclassified